1999
DOI: 10.1021/jp983305x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spectral Diffusion on the Line Shapes of Single CdSe Nanocrystallite Quantum Dots

Abstract: We study the emission line shapes of single CdSe nanocrystallite quantum dots. Single dot line shapes are found to result from rapid spectral shifting of the emission spectrum rather than the intrinsic physics of the quantum dot. A strong dependence of single dot line widths on excitation intensity, wavelength, temperature, and integration time is found and is correlated with the number of times that the quantum dot is excited during the acquisition of a single spectrum. The observed results are consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
264
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(285 citation statements)
references
References 31 publications
20
264
1
Order By: Relevance
“…4. Some of the spectra consist of only the NP line, sometimes homogeneously broadened by effects like spectral diffusion or scattering, 26 while others exhibit some or all of the aforementioned sidebands. Sychugov et al 19 report a blend of different spectra, some containing and some missing, e.g., TO-phonon replicas, and explain the dominance of zero-phonon transitions in silicon nanocrystal spectra by spatial localization of excitons, in addition to the quantum confinement effect.…”
Section: Fig 2 (Color Online) Pl Images and 50mentioning
confidence: 99%
“…4. Some of the spectra consist of only the NP line, sometimes homogeneously broadened by effects like spectral diffusion or scattering, 26 while others exhibit some or all of the aforementioned sidebands. Sychugov et al 19 report a blend of different spectra, some containing and some missing, e.g., TO-phonon replicas, and explain the dominance of zero-phonon transitions in silicon nanocrystal spectra by spatial localization of excitons, in addition to the quantum confinement effect.…”
Section: Fig 2 (Color Online) Pl Images and 50mentioning
confidence: 99%
“…13 This latter SD process is the most commonly studied and the most disruptive process due to the size of the spectral jumps and is the focus of this work. The spectral jumps have been attributed to individual charges moving around the surface, 14,15 although this attribution is merely speculative. For example, scanning electron force microscopy has shown that many, but not all, NCs have or develop surface charges, 16 while SD is a ubiquitous phenomenon observed in all single NC studies.…”
mentioning
confidence: 99%
“…18 Such an interpretation is compatible with the SD model originally proposed by Empedocles and Bawendi. 14 Early reports of SD in NCs revealed a thermal activation energy below which the SD process is solely photoactivated. 14,15 This motivates the study of SD at cryogenic temperatures, where competing thermal effects are eliminated, effectively isolating the photophysical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal variations in the peak emission wavelength are accompanied by, and correlated with, variations in the emission line width [285][286][287][288]. Most of the experiments into spectral diffusion were conducted at cryogenic temperatures [289][290][291][292], but the process occurs at room temperature, too [285][286][287][288]. A direct link between spectral diffusion and blinking was proposed, based on correlations between blinking events (on-off switches) and spectral shifts [290,293].…”
Section: Blinking Dynamics On Ms Timescales and Slowermentioning
confidence: 99%